2015
DOI: 10.1177/1941406415600752
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Increase Dairy Consumption in Adolescents

Abstract: Objective. Effective interventions are needed to address the reported inadequacies of dairy product and calcium (Ca) intakes among adolescents. The present review investigated interventions aimed at increasing adolescent dairy and/or Ca intakes and determined the characteristics associated with successful interventions. Design. A PRISMA systematic review search identified 17 interventions, described in 16 publications, between 1993 and 2015 (February). Studies were evaluated for population, delivery, dietary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
5
12
1
Order By: Relevance
“…Effectiveness was determined for 99 of the interventions, of which ∼82% were found to be effective at immediate follow‐up (Table ). This high proportion of effective studies supports results found from a similar systematic review of dietary interventions aimed to increase dairy and calcium intake among younger children (5‐12 years), as well as a review of dietary interventions to increase dairy and calcium intake among adolescents (12‐18 years) . A previous meta‐analysis which reviewed school‐based interventions also showed high efficacy in reducing obesity rates .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Effectiveness was determined for 99 of the interventions, of which ∼82% were found to be effective at immediate follow‐up (Table ). This high proportion of effective studies supports results found from a similar systematic review of dietary interventions aimed to increase dairy and calcium intake among younger children (5‐12 years), as well as a review of dietary interventions to increase dairy and calcium intake among adolescents (12‐18 years) . A previous meta‐analysis which reviewed school‐based interventions also showed high efficacy in reducing obesity rates .…”
Section: Discussionsupporting
confidence: 79%
“…Studies that achieved a higher intensity rating scored consistently well across all 4 measures. Based on previous research, we hypothesized that higher intensity interventions would be more effective than interventions with lower intensity; however, the data did not support this idea. As illustrated in Table , more than 80% of interventions irrespective of intensity were effective at immediate follow‐up, demonstrating a significant positive change in dietary behavior post‐intervention.…”
Section: Discussionmentioning
confidence: 89%
“…49 The findings of the present study should contribute to the development of future interventions by highlighting several potential targets to address when aiming to change dairy intake in adolescents and the potential difficulties in addressing these factors.…”
Section: Discussionmentioning
confidence: 85%
“…Clearly, there is an overrepresentation of school‐based knowledge measurement tools that maintain a more general approach. A concern, however, is that there is evidence to suggest that a more targeted nutritional focus may be more likely to result in positive dietary changes . The present study therefore highlights a need for valid and reliable tools that measure knowledge of specific foods or food groups, such as dairy and fruits and vegetables.…”
Section: Discussionmentioning
confidence: 84%
“…Notably, nutrition knowledge was usually not the exclusive outcome of the intervention, and most studies considered other variables such as dietary behavior or intentions. Search terms and databases were developed in consultation with a learning and curriculum support specialist and were informed by relevant and recent systematic reviews . Search terms used were comprehensive and inclusive and were categorized by the following 4 groupings: study type (eg, intervention); assessment tools (eg, nutrition, diet, knowledge); population (eg, youth, preadolescent, adolescent); and setting (eg, school, school‐based, primary school, high school).…”
Section: Methodsmentioning
confidence: 99%